Analysis of the coal and white leadtree wood co-firing needs as a primary fuel source in the anggrek gorontalo coal-steam electricity power plant (PLTU) - Wijaya, Bagus; Mohamad, Yasin; Matoka, Arifin; Irawaty Tolago, Ade (Universitas Muhammadiyah Surakarta, 2025)
The Anggrek coal-steam power plant (PLTU) in gorontalo is anpower generation facility that utilizes coal as its primary energy source. In recent years, the energy industry has undergone significant changes, driven by the need to reduce greenhouse gas emissions and increase the utilization of renewable energy souces. Dried white leadtree wood, exposed to sunlight for 18 hours, has a moisture content of 40% and a high calorific value of 4,197 kcal/kg, making it suitable for blending with coal. This power plant applies co-firing, which involves blending 1-5% white leadtree woodwith 1,000 tons of coal daily. This study aims to analyze the electricity generated. Additionally, this study evaluates the needs and procurement of both coal and white leadtree, alongside the sales of electricity in kWh. The methodology involvescollecting monthly data on fuel consumption and cost estimates per kWh generated. The results indicatevthat coal accounts for 95% of the total fuel consumption, while white leadtree contributes only 5%. The estimated cost of purchasing coal for co-firing with white leadstree is IDR 520 per kg, whereas the selling price of electricity is IDR 2.500 per kWh.